Cyclooxygenase-2-Derived Prostaglandins Mediate Cerebral Microcirculation in a Juvenile Ischemic Rat Model. Issue 12 (December 2016) - Leger, Pierre-Louis; Pansiot, Julien; Besson, Valerie; Palmier, Bruno; Renolleau, Sylvain; Baud, Olivier; Cauli, Bruno; Charriaut-Marlangue, Christiane
Abstract : Background and Purpose—: We previously showed that the selective neuronal nitric oxide synthase inhibitor 7-nitroindazole (7-NI) increases cerebral microcirculation in a juvenile ischemic rat model. We address the roles of cyclooxygenase (COX)-elaborated prostaglandins in collateral recruitment and blood supply. Methods—: Fourteen-day-old rats were subjected to ischemia–reperfusion and treated with either PBS or 7-NI (25 mg/kg) at the reperfusion onset. Six-keto-prostaglandin F1α was measured using ELISA. COX-1 and COX-2 and prostaglandin terminal synthesizing enzymes were evaluated using reverse-transcriptase polymerase chain reaction and immunofluorescence. Microvascular blood flow indexes (artery diameter and capillaries number) were measured using sidestream dark-field videomicroscopy in PBS- and 7-NI-treated ischemic rats in the absence or presence of the COX-2 inhibitor NS-398 (5 mg/kg). Cell death was measured with the TUNEL (terminal transferase dUTP nick end labeling) assay and cleaved-caspase-3 immunostaining. Results—: Six-keto-prostaglandin F1α and COX-2, associated with a prostaglandin E synthase, were significantly increased in PBS- and 7-NI-treated animals 15 minutes and 1 hour after ischemia–reperfusion, respectively. In contrast and as compared with PBS, 7-NI significantly decreased prostacyclin synthase and cytosolic prostaglandins E synthase mRNA. Selective COX-2 inhibition significantly decreased blood flow indexes and significantly reversed the effects of 7-NI, including the number of TUNEL + - and cleaved-caspase-3 + -nuclei. Conclusions—: These results show that the juvenile rat brains mostly respond to ischemia by a COX-2-dependent prostaglandins production and suggest that the transcriptional responses observed under 7-NI facilitate and reorient COX-2-dependent prostaglandins production. Abstract : Supplemental Digital Content is available in the text.